Tenofovir disoproxil fumarate fails to prevent HIV acquisition or the establishment of a viral reservoir: two case reports - Fox, J; Brady, M; Alexander, H; Davies, O; Robinson, N; Pace, M; Else, L; Cason, J; Khoo, S; Back, D; Fidler, S; Frater, A (Springer Healthcare, 2016)
The use of antiretrovirals as pre-exposure prophylaxis (PrEP) is highly efficacious in HIV prevention. The World Health Organization recently recommended Truvada(®) (Gilead Sciences, Inc.) or tenofovir disoproxil fumarate (TDF) for high-risk individuals, with limited data for single-agent TDF PrEP in men who have sex with men (MSM). We report two cases of TDF PrEP failure in MSM who had received long-term TDF for hepatitis B infection and had therapeutic levels of drug immediately after HIV acquisition. Rapid antiretroviral intensification at diagnosis of acute HIV infection failed to limit immune dysfunction or prevent the establishment of a viral reservoir.